Activity of Antiseptics Against Pseudomonas aeruginosa and Its Adaptation Potential - Tomasz M. Karpiński; Marzena Korbecka-Paczkowska; Mark Stasiewicz; Aleksandra E. Mrozikiewicz; Donald Włodkowic; Judyta Cielecka-Piontek (Antibiotics)
Background/Objectives: Pseudomonas aeruginosa rapidly acquires antibiotic resistance and demonstrates increasing tolerance to antiseptics. This study evaluated the activity of eight antiseptics against P. aeruginosa, assessed its ability to develop adaptation to these antiseptics, and, for the first time, determined the Karpinski Adaptation Index (KAI) for this bacterium. Methods: The minimal inhibitory concentration (MIC), susceptibility to antibiotics, bactericidal time according to EN 1040:2005, adaptation potential, and KAI of P. aeruginosa strains were evaluated. Results: The most effective antiseptics against P. aeruginosa, based on MIC activity, were octenidine dihydrochloride (OCT; mean MIC 11.3 ± 4.5 µg/mL), polyhexamethylene biguanide (PHMB; MIC 22.6 ± 8.0 µg/mL), and chlorhexidine digluconate (CHX; MIC 26.6 ± 14.4 µg/mL). Sodium hypochlorite (NaOCl) and ethacridine lactate (ET) showed moderate activity, while boric acid (BA), povidone-iodine (PVI), and potassium permanganate (KMnO4) exhibited the weakest MIC activity. MIC values for NaOCl (95 ± 15.4 µg/mL) and KMnO4 (>10 mg/mL) were close to or exceeded the clinical concentrations used in commercial products. OCT, CHX, and PVI exhibited the fastest bactericidal effect within 1 min. Bactericidal times were up to 15 min for PHMB, up to 60 min for ET, and more than 60 min for BA, NaOCl, and KMnO4. The lowest KAI values, indicating a low resistance risk, were observed for OCT (0.12), PHMB (0.19), and BA (0.19). Moderate resistance risk was noted for PVI (0.21), CHX (0.29), and ET (0.47). The highest KAI values, signifying a very high resistance risk, were found for NaOCl (1.0) and KMnO4 (≥1.0). Conclusions: Antiseptics like OCT, CHX, and partially PVI can be critical in quick antibacterial action on infected wounds, while agents such as PHMB might be reserved for cases where prolonged contact times are possible. Given the rapid adaptation of P. aeruginosa to the clinical concentrations of NaOCl and KMnO4 currently in use, reconsideration of their effectiveness in treating skin and mucous membrane infections is recommended.